People-Centred Public Health - South, Jane; Gamsu, Mark; White, Judy (Lecturer in health promotion) (Book collections on Project MUSE., 2013)
People-centred public health provides a comprehensive and accessible overview of policy, practice and research in how members of the public can be involved in delivering health improvement as volunteers or lay health workers, drawing on a major study of lay engagement in public health, and using case studies and real life examples.